Evaluasi Pelaksanaan Overhaul Pabrik Indarung VI Pada Masa Pandemu di Tahun 2020 - Ridwan Muchtar; Benny Dwika Leonanda (Jurnal Teknik Mesin, 2022)
Overhaul activity is one periodic maintenance by the company to recondition production equipment in order tooperate with high avaibility and realibility. Overhaul activities can also be referred to as project based on a series of work that occirs unique, complex, done in a certain period of time and resources. This factory overhaul project must be completed on time, according to quality and cost as well as zero accident. In connection with the condition of the Covid-19 pandemic, the work is carried out with the Covid-19 health protocol so that ts doesnot become a source of new spread. In this paper will be discussed the implementation of the overhaul of theplant Indarung VI Year 2020 in the pandemic, starting from the stages of planning, preparation, implementation and evaluation (feedback). The realization of work time experienced delays of 2,68 days, quality according to standards and with the realization of a greater cost of Rp. 2.22 Billion. During the overhaul project there were 3 cases of work accidents and there were no additional cases of Covid-19 in the workforce involved in the project.